Video Mapping for Sea Turtle Preservation Education Campaign - et.al, Annisha Muhtadini Fajri (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to produce video mapping design concept to educate the topic on sea turtle conservation for all levels of Indonesian societies, especially in the Jakarta Aquarium recreation facilities. Indonesia, a tropical country with variety of natural resources and habitat of the endangered sea turtles required a protection on their habitat by the government. There are 6 types of sea turtles spread across the vast 138 different waters in Indonesia. Efforts of preservation as part of the world's ecosystem need to be done by various parties. The Visual Communication Design, as a major whom proficient in the perceptive communication language has a big role in delivering the message and exploring media for public education about the importance of maintaining the balance of the turtle ecosystem. Video mapping or projection art, is a contemporary technique of delivering information through visual images using lighting and projection so as to produce optical illusions on the object being directed. Through visual communication design method, the result is a video mapping design concept to display a provoking animation meant to visualize the grueling condition and survivability of sea turtles in recent years and to gain awareness for preserving and protecting the natural environment. The video mapping design concept can be used for environmental issues learning materials for youth.